Analysis of BKO Content (Antalgin and Dexamethasone) in Herbal Medicine Using Iodimetry Titration and HPLC Method - Agus Dwi Ananto; Lalu Undrus Yusditia M. G; Lalu Sanik Wahyu F. A (Elkawnie: Journal of Islamic Science and Technology, 2020)
Abstract : Misuse of adding chemical drugs – BKO – into herbal medicines is often done by irresponsible people. The aim is to increase efficacy instantly, to attract consumer interest. BKO, which are often added to herbal medicine, are antalgin and dexamethasone. Antalgin content analysis was carried out quantitatively using the iodimetry titration method by conducting a preliminary test. The dexamethasone content analysis was carried out with qualitative and quantitative methods. The qualitative method was carried out using TLC. The quantitative method was carried out using the HPLC technique. The results obtained for the analysis of antalgin content of 10 samples were obtained two samples of herbal medicine containing antalgin, respectively 0,0749% and 0,1083%. Analysis of the dexamethasone content from 10 samples obtained 5 herbal samples containing dexamethasone respectively 0.0979%, 0.222%, 0.4521%, 0.5131% and 0.2809%. So based on these results, it is necessary to take action from the relevant institution regarding the discovery of the content of BKO in the herbal medicine on the market in Lombok.Abstrak : Penyalahgunaan penambahan bahan kimia obat (BKO) kedalam jamu sering sekali dilakukan oleh oknum yang tidak bertanggung jawab. Hal ini dilakukan dengan tujuan meningkatkan khasiat secara instan, sehingga dapat menarik minat konsumen. BKO yang sering ditambahkan kedalam jamu adalah antalgin dan deksametason. Analisis kandungan antalgin dlakukan dengan cara kuantitatif menggunakan metode titrasi iodimetri dengan melakukan uji pendahuluan. Sedangkan analisis kandungan deksametason dilakukan dengan metode kualitatif dan kuantitatif. Metode kualitatif dilakukan dengan menggunakan KLT. Metode kuantitatif dilakukan dengan menggunakan teknik HPLC. Hasil yang diperoleh untuk analisis kandungan antalgin dari 10 sampel didapat 2 sampel jamu yang mengandung antalgin masing-masing sebesar 0,0749% dan 0,1083%. Analisis kandungan deksametason dari 10 sampel diperoleh 5 sampel jamu yang mengandung deksametason masing masing sebesar 0,0979%; 0,222%; 0,4521%; 0,5131% dan 0,2809%. Sehingga berdasarkan hasil tersebut maka perlu dilakukan adanya tindakan dari instansi terkait perihal masih ditemukannya kandungan BKO dalam sediaan jamu yang beredar di pasaran pulau Lombok.